2021
DOI: 10.3390/ma14237107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Simultaneous Sintering of Bioglass to a Zirconia Core on Properties and Bond Strength

Abstract: This study aimed to assess bioglass sintering to a zirconia core on surface properties and bonding strength to resin cement. Zirconia specimens were divided into four groups: G I: sintered; G II: bioglass modified zirconia (a bioglass slurry was sintered with zirconia at 1550 °C); G III: sandblasted using 50 μm Al2O3 particles; and G IV: Z-prime plus application. Surface morphology and chemical analysis were studied using a scanning electron microscope and energy-dispersive spectroscopy. Surface roughness was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…7,[33][34][35] Previous studies have shown that the zirconia surface promotes increased osseointegration rates and reduced adhesion of pathogenic microorganisms. 33,[36][37][38] To enhance these properties, bioactive glass layers have been added to the zirconia surface to improve bond strength and biological response. [39][40][41] Bioglass 45S5, known as bioglass, is a biomaterial developed by Larry Hench in 1969, to promote a fast and durable chemical bond with bone tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,[33][34][35] Previous studies have shown that the zirconia surface promotes increased osseointegration rates and reduced adhesion of pathogenic microorganisms. 33,[36][37][38] To enhance these properties, bioactive glass layers have been added to the zirconia surface to improve bond strength and biological response. [39][40][41] Bioglass 45S5, known as bioglass, is a biomaterial developed by Larry Hench in 1969, to promote a fast and durable chemical bond with bone tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Zirconia is an example of ceramic material 4,5,32 widely used in dentistry and orthopedics due to its excellent chemical stability, high strength, fracture toughness, and aesthetic properties 7,33–35 . Previous studies have shown that the zirconia surface promotes increased osseointegration rates and reduced adhesion of pathogenic microorganisms 33,36–38 . To enhance these properties, bioactive glass layers have been added to the zirconia surface to improve bond strength and biological response 39–41 …”
Section: Discussionmentioning
confidence: 99%
“…The formation of crystalline phases is influenced by particle size and the CaO/SiO2 ratio (Dávalos et al, 2020). Glass-crystalline materials based on bioglasses belong to bioactivity class A, showing high biological reactivity and have very good mechanical properties, exceeding the parent glass in terms of hardness, bending strength and crack resistance (El-Wassefy et al, 2021). When the glass-ceramic material is immersed in the SBF solution, three processes occur successively: leaching (a), dissolution (b) and precipitation (c) -Fig.…”
Section: Bioactivity and Properties Of Glass-ceramic Biomaterialsmentioning
confidence: 99%
“…This layer serves as a chemically reactive surface that can be etched and primed [ 9 , 10 ]. Different types of ceramic coatings have been used for this purpose [ 8 , 11 - 13 ], however, due to the lack of studies in this regard, further investigation of ceramic coatings on the inner surface of zirconia is encouraged [ 8 ]. In some studies, bioglass coatings on zirconia implants have been successfully used to benefit from the bioactive properties of bioglass and the mechanical properties of zirconia [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%